Early and mid-term outcomes after transcatheter aortic valve implantation (TAVI) in Ireland. (September 2017) - Bajrangee, A.; Coughlan, J.J.; Teehan, S.; O'Connor, C.; Murphy, R.T.; Foley, B.; Daly, C.; Burke, D.; Maree, A.O.; Crean, P.A.
Abstract: Background: TAVI is a percutaneous approach to aortic valve replacement in high surgical risk patients deemed inoperable. Aim: To evaluate the early and mid-term outcomes for an Irish TAVI cohort over a six-year period at St James's Hospital and Blackrock Clinic, Dublin, Ireland. Results: In total 147 patients, 56% male with an average age of 82 underwent TAVI between December 2008 and December 2014. Thirty day, one year and two year survival was 90.5%, 83% and 71% respectively. Major vascular complications and renal failure were the biggest predictors of mortality at 30 days (p = 0.02). We observed a pacing rate of 13.5%, the majority in patients who had Medtronic Corevalve implants (p < 0.05). With increasing procedural experience there was a reduction in length of stay from 10 days to 7.5 days. Conclusion: This review, the first of its kind in Ireland showed favorable rates of 30 day and one year and two year survival post TAVI with procedural success and complication rates similar to international registry data.